Lost in transition: life satisfaction on the road to capitalism - Richard A. Easterlin (Institute for the Study of Labor (IZA), 2008)
In the transition from socialism to capitalism in Eastern Europe life satisfaction has followed the V-shaped pattern of GDP but failed to recover commensurately. In general, increased satisfaction with material living levels has occurred at the expense of decreased satisfaction with work, health, and family life. Disparities in life satisfaction have increased markedly with those hardest hit being the less educated and persons over age 30; women and men have suffered about equally. The asymmetric response of life satisfaction to decreases in GDP in transition countries and increases in GDP in non-transition countries is arguably due to loss aversion.
urn:nbn:de:101:1-20080320119
Keywords: I31; 330; Happiness; transition; capitalism; socialism; loss aversion; Lebenszufriedenheit; Lebensqualität; Übergangswirtschaft; Lebensstandard; Risikoaversion; Osteuropa